Aimai dalam Anime Flying Witch: Kajian Sosiopragmatik - Devi Haryanti Oktavia; Mangatur Sinaga; Intan Suri (Publikasi Indonesia, 2022)
Language and culture are two things that cannot be separated. The culture in a society of every nation is different. These cultures will affect how people communicate. One of the cultures that influence Japanese communication is the Aimai. Aimai is defined as a situation in which there is more than one intended meaning resulting in ambiguity, gloom, and uncertainty. Aimai used in communication aims to maintain harmony in social life. This study aims to examine the Aimai in the flying witch anime. This research is a qualitative descriptive study. The data collection method used is the listening method with the basic technique in the form of tapping techniques and the advanced technique is the note-taking technique.data of this research is the dialogue between the characters in the flying witch anime directed by Katsusi Sakurabi. This research found 33 data containing Aimai where the Aimai that appear are words, expressions, and sentences. The data that appears the most is Aimai in the form of interrogative sentences with kana, this is indicated by the discovery of 13 data containing kana. While the least is Aimai in the form of sentences with the kanji tte where only 1 data is found. After analyzing the data, it can be concluded that the forms of Aimai in Japanese communication can be in the form of words, expressions, and sentences